1992
DOI: 10.1002/jor.1100100214
|View full text |Cite
|
Sign up to set email alerts
|

The microstructural tensile properties and biochemical composition of the bovine distal femoral growth plate

Abstract: The tensile properties of distal femoral growth plates from 12-month-old cows were determined on uniformly prepared straight bone-growth plate-bone specimens (7 x 7 mm2 in cross-section) from predetermined anatomical sites on the physis. Each specimen was distracted to failure using a computer-controlled servo-hydraulic testing machine at a strain rate of 0.004 s-1. It was found that the exponential constitutive law, using finite deformation formulation for strain, provides an excellent description of the stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 27 publications
3
44
1
Order By: Relevance
“…After overnight incubation at 37Ā°C, the sponges were subjected to 5% elongation at 60 cycles/min, 15 min/h, by a computer-controlled Biostretch device (ICCT Technologies, Canada). This extent of matrix deformation may be comparable to that experienced in a growth plate in vivo (28). Biostretch exerts a uniaxial stretch with square wave patterns.…”
Section: Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…After overnight incubation at 37Ā°C, the sponges were subjected to 5% elongation at 60 cycles/min, 15 min/h, by a computer-controlled Biostretch device (ICCT Technologies, Canada). This extent of matrix deformation may be comparable to that experienced in a growth plate in vivo (28). Biostretch exerts a uniaxial stretch with square wave patterns.…”
Section: Methodsmentioning
confidence: 64%
“…We tested this hypothesis in a new three-dimensional chondrocyte culture system that we established recently (27). In this system, primary chondrocytes from developing chick cartilage were cultured in a sponge of collagen networks to which cyclic mechanical stress was applied by a computer-controlled "Bio-stretcher" device (27), thereby mimicking the mechanical stimulation developing cartilage experiences in vivo (28). Our results show that mechanical stress induces the expression of Ihh, which in turn transduces the mechanical signals in a BMP-dependent manner to stimulate chondrocyte proliferation.…”
mentioning
confidence: 99%
“…4c,d). Similarly, in comparison with articular cartilage, a higher tendency to grow is expected in cartilage of the growth plate where the proportion of GAG is higher and tensile strength and modulus are lower than those of articular cartilage (Cohen et al 1992;Nakano and Sim 1995). Indeed, a relatively high rate of axial growth is observed in the growth plate in vivo (up to āˆ¼400 Āµm/day) (Wilsman et al 1996), as well as in vitro where larger increases in length were observed in cartilages containing one or more osteogenic zones as compared to that of entirely cartilaginous explants (Copray et al 1986).…”
Section: Discussionmentioning
confidence: 94%
“…It is still completely unknown whether these pericliondrialperiosteal elastic fibres contribute to the mechanical competence of the collagen network in resisting to both physiological and pathological loading [2,5,50], and in regulating long bone growth [6,12,22,31,33]. Some recent observations of a dramatic reduction of perichondrial-periosteal elastic fibres in human and bovine Marfan syndromes led us to hypothesize that skeletal overgrowth, typical of this disorder, may be related to alterations of elastic fibres and of their microfibrillar component [19,20,27], the Marfan syndrome being a genetric disorder caused by mutations of the fibrillin-1 gene, a major constituent of elastin-associated microfibrils [ 131.…”
Section: Biochemistrymentioning
confidence: 99%
“…Extensive attention has been given to the latter, i.e., vascular supply, perichondrial-periosteal connective tissue and muscular activity [3,6,23,25,32,33,35,49,51,53]. It has been shown that experimental interference with the subchondral vascularisation has no effect on longitudinal skeletal growth; moreover, the legation of nutrient artery has only limited curbing effect on bones [31].…”
Section: Introductionmentioning
confidence: 99%